2014
DOI: 10.3103/s0361521914040089
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of humic acids by quartz sands

Abstract: The sorption of humic acids on different types of silicon containing materials was studied. It was shown that the interaction of humic acid fragments with a mineral surface depends on acid-base and surface active properties and on the composition of the mineral sorbent surface. An increase in the aluminum content of the sorbent strengthens the interaction of humic substances with the mineral surface. It was established that the humic acids of peat were better sorbed on the silicon containing surface due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Faisal et al (2020) showed that plantation of humic acid nanoparticles on inert sand increased the sorption capacity of Cu. The minerogenic composition differs between different types of sand, which can affect the interaction of humic substances with the mineral surface (Mal'tseva & Yudina 2014). The implication of this relationship is that selected sand for filtration can affect the outcome of the removal of the metals.…”
Section: Presence and Removal And Ratio Between Total And Dissolved F...mentioning
confidence: 99%
“…Faisal et al (2020) showed that plantation of humic acid nanoparticles on inert sand increased the sorption capacity of Cu. The minerogenic composition differs between different types of sand, which can affect the interaction of humic substances with the mineral surface (Mal'tseva & Yudina 2014). The implication of this relationship is that selected sand for filtration can affect the outcome of the removal of the metals.…”
Section: Presence and Removal And Ratio Between Total And Dissolved F...mentioning
confidence: 99%